1×2 optical switch for indoor LAN - Bhuiyan, Moinul; Haga, Yoichi; Bhuiyan, Munira; Esashi, Masayoshi (2013)
Polymer optical fiber (POF) is suitable for indoor local area network (LAN), because of its flexibility and its ease of connection due to its relatively large core diameter. A 1×2 optical switch for indoor LAN using POF and a shape memory alloy (SMA) coil actuator with magnetic latches was successfully fabricated and tested. To achieve switching by the movement of a POF, large displacement is necessary because the core diameter is large (e.g., 0.486mm). A SMA coil actuator is used for large displacement and a magnetic latching system is used for fixing the position of the shifted POF. The insertion loss is 0.40 to 0.50dB and crosstalk is more than 50dB without index-matching oil. Switching speed is less than 0.5s at a driving current of 80mA. A cycling test was performed 1.4 million times. Polymer clad fiber optical (PCF) switch also fabricated and tasted.